The rise of mental health nursing : a history of psychiatric care in Dutch asylums, 1890-1920 - Boschma, Geertje (Amsterdam University Press, 2003)
A unique analysis of psychiatric care and the emerging field of mental health nursing in the Netherlands at the turn of the 19th century.